A Review of "The Marrow of Longing" by Celeste Nazeli Snowber - Mantas, Kathy (Art/Research International)

(untitled) (University of Alberta, 2022)
This is a review of The Marrow of Longing by dancer/poet/writer/educator, Celeste Nazeli Snowber. This book, presented in fragments, is a heartrending and thought-provoking poetic and visual inquiry into Celeste’s motherline, Armenian cultural heritage, and identity. It will awaken, like it has for me, your longings and need to become aware of what has formed and informed your own life. The Marrow of Longing is both an offering/gift and an invitation.